Analisis Kesulitan Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XI IPS Di SMA Negeri 6 Kota Bengkulu - Duharman Duharman; Bahrin Bahrin; Agnes Rosalia (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This research aims to identify students' difficulties in studying economics subjects in class XI IPS at SMAN 6 Bengkulu City and identify factors that cause learning difficulties in economics subjects at SMA Negeri 6 Bengkulu City. This type of research is qualitative descriptive research. The population in this research is all Class people, IPS D 32 people and IPS E 35 people. Data collection techniques use observation, interviews and documentation. The results of the research show that there are quite a lot of difficulties in studying economics subjects in class that most students experience difficulties in various aspects of economics learning.